Problematics of Legal Politics in the Formation of Legislation in Indonesia - Ali Yusran Gea (JURNAL AKTA, 2024)
Legal Politics of Legislation experiences problems both in terms of formation, political aspects, philosophical aspects, sociology and juridical aspects so that the formation of Legislation is greatly influenced by the tug-of-war of interests, both the political interests of the executive power, the political interests of the legislative power and the political interests of the judiciary. The legal implications related to the existence of Legal Politics problems in the formation of Legislation give birth to Legislation that is not of good quality so that the law enforcement process experiences a decline and is not legal certainty. Legislation as the basis for every implementation of government activities where Legislation is a part or subsystem of the legal system. The process of forming Legislation is part of the legal political process and plays a significant role in the development of national law. The formation of Legislation both in the planning, drafting, and discussion stages of the draft Legislation really needs the active role of the community. The problematic factors of legal politics in the formation of legislation include Legal Factors and Non-Legal Factors where legal factors include those that are contrary to the Constitution [1945 Constitution], contrary to the law, overlapping, contrary to legal norms and procedures that are contrary to Law No. 12 of 2011 concerning the Formation of Legislation, while non-legal factors include political factors, economic factors, social factors and cultural factors. Apart from legal and non-legal factors, the content of the legislation is also far from philosophical, sociological and juridical values.